Determinants of Entrepreneurial Skill Acquisition among Agricultural Students in Nigeria Universities in Ogun State, Nigeria. - Onasanya, A. S.; Onasanya, O. A.; Aderinto, A. (NIU Journal of Humanities, 2017)
Entrepreneurial skill acquisition among agricultural students in Nigeria Universities has been of major concern due to explosion rate of unemployment in the country and this formed the basis for the study in Ogun State. Forty (40) students were purposefully selected University of Agriculture, Tai Solarin University of Education and Olabisi Onabanjo University making a total of 120 students as the study sample. The findings revealed that majority of the students were in the age grade of 21 â€“ 24 years (63.1%), male (71.7%), Christian (52.5%) and from Department of Agricultural Economics, Agricultural Extension, Home and Hotel Management, Animal Production, Crop production, Soil Science and Farm Mechanization and Renewable Resources. Majority of the respondents posited that they had acquired entrepreneurial skills in animal and crop production among others. Also, the students posited that they have leadership skill, self confidence, ability to organize resources to achieve goals, innovate and speculate, have need for achievement and success in skill acquired and lastly possess strong desire for responsibility and independence respectively. The study concludes that 70.8% of the students agreed that the level of the skill acquired determined their efficiency as entrepreneur. The study  therefore recommended that economic policy and programs that are geared towards self reliance for individuals such as Open Apprenticeship Scheme, Graduate Employment Programs etc and other policies that encourage or make it easy for entrepreneurs to acquire the needed funds especially graduates from Universities. Keywords: Entrepreneur, Skill acquisition, Agriculture, Students, Universities